Breast cancer mortality among patients attending a cancer hospital, Vitoria, ES - Cristina Arthmar Mentz Albrecht; Maria Helena Costa Amorim; Eliana Zandonade; Kátia Viana; Juliana Oliosi Calheiros (Associação Brasileira de Pós-Graduação em Saúde Coletiva, 2013)
This study aimed to investigate the association between mortality of breast cancer women and the social-demographic and clinical characteristics. During the mortality study of 1,086 women diagnosed with breast cancer and treated from 2000 to 2005 at a cancer hospital in the city of Vitória, Espírito Santo, medical records and tumor registration cards were controlled. The Mortality Information System and the Reclink program were used to identify 280 deaths. Patients were classified under death and non-death, and variables percentages were calculated. For variables that showed statistical significance, considering the level of 0.10, the crude and adjusted odds ratio (OR) were calculated by logistic regression model. There was a correlation between mortality and the following variables: women coming from the Unified Health System (p = 0.014; OR = 2.38), negative c-erb B-2 tumor marker (p = 0.027; OR = 2.03), advanced (III and IV) staging (p = 0.001; OR = 6.89 and OR = 17.13, respectively), presence of metastasis (p = 0.001; OR = 18.23) and recurrence (p = 0.010; OR = 3.53). Mortality associated with staging underlines the necessity of warning the population about the benefits of early diagnosis of the disease of cancer.